2013
DOI: 10.1186/1471-2431-13-80
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic controlled trial to prevent childhood obesity in maternity and child health care clinics: pregnancy and infant weight outcomes (The VACOPP Study)

Abstract: BackgroundAccording to current evidence, the prevention of obesity should start early in life. Even the prenatal environment may expose a child to unhealthy weight gain; maternal gestational diabetes is known to be among the prenatal risk factors conducive to obesity. Here we report the effects of antenatal dietary and physical activity counselling on pregnancy and infant weight gain outcomes.MethodsThe study was a non-randomised controlled pragmatic trial aiming to prevent childhood obesity, the setting being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 49 publications
3
52
0
1
Order By: Relevance
“…14,19,3436,38,39 However, behavior change counseling provided in the clinical setting is necessarily limited in its impact on individual and family lifestyles by manifold non-medical, but health-critical, influences from the social and physical environment— factors that are highlighted by the ecosocial 52 and Glass and McAtee 53 conceptual frameworks discussed above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,19,3436,38,39 However, behavior change counseling provided in the clinical setting is necessarily limited in its impact on individual and family lifestyles by manifold non-medical, but health-critical, influences from the social and physical environment— factors that are highlighted by the ecosocial 52 and Glass and McAtee 53 conceptual frameworks discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The Vaasa Childhood Obesity Primary Prevention Study provided education on maternal and child diet and physical activity at prenatal visits, group sessions, and well child visits, but did not demonstrate an effect on child growth measures through age 12 months. 19 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…Similar to our study, the few studies that have reported on infant growth after prenatal interventions have found no changes in infant growth. This includes two previous European studies with null results 27,28 and one study in the United States evaluating a walking intervention during pregnancy that followed babies to 6 months postpartum. 29 Biological explanations for these null findings have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…В некоторых странах подготовлены специальные программы по профилактике ожирения для работы с беременными и матерями в женских консультаци-ях и детских поликлиниках [19]. Известно, что масса ребенка при рождении более 4 000 увеличивает риск развития ожирения у взрослых в 2 раза [20], а кон-сультирование беременных уменьшает риск рожде-ния детей с массой тела более 4 000 г.…”
unclassified